1986
DOI: 10.1159/000183991
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Aldosterone and Sodium, Potassium, and Uric Acid Clearance in Cirrhosis with and without Ascites

Abstract: We have suggested that cirrhotic patients with high uric acid clearances had an increased effective vascular volume. This hypothesis was tested by studying the relationship between the excretion of uric acid, sodium, potassium, and aldosterone in cirrhosis. In 29 consecutive cirrhotic patients, of whom 17 had ascites, and in a control group, the logarithm of urinary sodium and aldosterone excretion highly correlated in control (r = – 0.79, p < 0.001) and cirrhotic patients without (r= – 0.72, p < O.Ol) and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Pa nel A of figure 2 shows a normal relationship between 24-hour urinary aldosterone and 24-hour natriuresis. Panel B demonstrates a correlation between urinary aldosterone excretion rate (log) and kaliuria studied by the urinary ratio U k/G k + ns comparable to that obtained formerly in our controls [24], The ANP level is in the low normal range at basal state (2.9 fmol/ml) and demon strates a slight increase during the water loading test (3.04 fmol/ml at 30 min. 3.15 at 60 min, 3.23 at 90 min.…”
Section: Hypotonic Saline Diuresissupporting
confidence: 83%
See 2 more Smart Citations
“…Pa nel A of figure 2 shows a normal relationship between 24-hour urinary aldosterone and 24-hour natriuresis. Panel B demonstrates a correlation between urinary aldosterone excretion rate (log) and kaliuria studied by the urinary ratio U k/G k + ns comparable to that obtained formerly in our controls [24], The ANP level is in the low normal range at basal state (2.9 fmol/ml) and demon strates a slight increase during the water loading test (3.04 fmol/ml at 30 min. 3.15 at 60 min, 3.23 at 90 min.…”
Section: Hypotonic Saline Diuresissupporting
confidence: 83%
“…The aldosterone secretion is, on the one hand, increased by the renin-angiotensin system, itself activated by the sodium chloride negative balance and by hypokalemia, and, on the other hand, inhibited by hypokalemia. In our patient, analysis of figure 2 panel A indicates that a nor mal relationship is maintained between urinary aldoste rone and sodium excretion [24]. Moreover, our patient, as 2 others studied in the same way [41], presents an appropriate relation between urinary aldosterone and the urinary ratio U k/U« + Na ( fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…23 To reconcile these findings, it has been proposed that aldosterone sensitivity was increased in cirrhosis. [24][25][26][27] This apparent high sensitivity to aldosterone might be accounted for in fact by the abnormal activation of MR by glucocorticoids. Supporting this hypothesis was the finding that 11␤ hydroxysteroid dehydrogenase type 2 (11␤ -HSD2) activity, which prevents access of glucocorticoids to MRs, 28 is decreased in cirrhosis.…”
mentioning
confidence: 99%
“…Several independent groups of investigators demonstrated that for a given renal sodium excretion the values for aldosterone were too low in patients with cirrhosis and therefore hypothesized that these findings are explained by an increased renal tubular sensitivity to aldosterone. [10][11][12] Here, the evidence is given for another hypothetical mechanism, which might mimic the presumed increased renal tubular sensitivity to aldosterone, i.e., the presence of a MRactivating ligand other than aldosterone. This ligand is most likely cortisol.…”
mentioning
confidence: 99%